Identifikasi Synaptula (Echinodermata : Holothuroidea) Raja Ampat Berdasarkan Gen COI - Robitoh Desi Kurniasari; Aris Soewondo (University of Brawijaya, 2014)
Identification of species Raja Ampat required in order to obtain marine biodiversity in Raja Ampat. Synaptula is one of the organism that inhabit in Raja Ampat and belonging to sea cucumber. Sea cucumber is an organism that difficult to distinguish through morphological characteristic.. This study aimed to identify Synaptula from Raja Ampat based on mitochondrial gene, cytochrome c oxidase subunit 1 (COI). The results of the study that Synaptula of Raja Ampat (UNP 101) is Plakobranchus ocellatus, the result is different with identification through morphological. Synaptula of Raja Ampat (UNP 101) has a high similarity with Plakobranchus ocellatus species from Sulawesi and the Philippines. Genetic distance Synaptula of Raja Ampat (UNP 101) with Synaptula reciprocans is 76.8%, while similarity values is 23.6%. The difference in the results of species identification may be caused by contamination DNA Plakobranchus UNP 67A to DNA Synaptula UNP 101, contamination is likely to occur during the identification process which simultaneity. Keywords: COI gene, identification, Synaptula.